2012
DOI: 10.1539/joh.11-0211-oa
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Outcome of Injured Workers at 3 Months after Occupational Injury Requiring Hospitalization in Taiwan

Abstract: Kuan-Han LIN, et al.: Psychological Outcome after Occupational Injury among workers who suffered from intracranial injury, fracture, burn, crushing injury, and open wound of upper limbs were 10.4, 6.9, 5.9, 5.8 and 0%, respectively. Conclusions: At three months after occupational injuries, a significant proportion of workers suffered from psychiatric disorders. The rates of psychiatric disorders occurring after intracranial injuries were significantly higher than those occurring after non-intracranial injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Kappa coefficients between scores on the MINI and the Composite International Diagnostic Interview, a similar measure, have been found to be acceptable (Lecrubier et al , 1997 ). The MINI was administered over the telephone, as has been done in prior studies (Lin et al , 2012 ; Shvartzman et al 2005 ), which have reported acceptable reliability but have not made validity data for this modality available.…”
Section: Methodsmentioning
confidence: 99%
“…Kappa coefficients between scores on the MINI and the Composite International Diagnostic Interview, a similar measure, have been found to be acceptable (Lecrubier et al , 1997 ). The MINI was administered over the telephone, as has been done in prior studies (Lin et al , 2012 ; Shvartzman et al 2005 ), which have reported acceptable reliability but have not made validity data for this modality available.…”
Section: Methodsmentioning
confidence: 99%
“…50 Kappa coefficients between scores on the MINI and the Composite International Diagnostic Interview have been found to be acceptable. 50 The MINI was administered over the telephone, as has been done in prior studies, [51][52][53] which have reported acceptable reli-ability but have not made validity data for this modality available.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study [5,24], we recruited 4403 workers with occupational injuries who had been hospitalized for 3 days or longer and who had received occupational inpatient compensation from the National Labor Insurance scheme of Taiwan between 1 February and 31 August 2009. A structured questionnaire survey was conducted 3 and 12 months after occupational injury; a total of 2308 injured workers completed the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Each year approximately 317 million nonfatal occupational injuries occur globally [2]. A certain proportion of workers develop psychiatric disorders [3,4,5] and suicidality [6] after occupational injury. Moreover, these conditions may last for more than several years [7].…”
Section: Introductionmentioning
confidence: 99%